Violência interpessoal contra a pessoa adulta no Espírito Santo: uma análise dos casos notificados entre 2011 e 2018 - Fiorotti, Karina Fardin (2023)
Introduction: Violence is an important public health problem, and its detailed analysis has both social and academic importance. Its magnitude and impacts highlight the need for integrated actions that minimize the effects of this problem on populations. Objective: To identify the frequency of different types of interpersonal violence in the adult population and analyze their association with the characteristics of the victim, the aggressor and the occurrence. Methods: This is an epidemiological, analytical, and cross-sectional study, carried out with cases of interpersonal violence in the years 2011 to 2018, in adults between 20 and 59 years old notified in the state of Espírito Santo in the System of Information of Diseases and Notification. The dependent variable was violence - of the sexual, psychological, physical and repetitive nature – and the independent variables were the characteristics of the victim, the aggressor and the occurrence. The study was approved by the Research Ethics Committee. Data analysis was performed using the Stata program version 14.1 and the Poisson regression results presented by the prevalence ratio. Results: Physical violence against adults was responsible for 63.3% of reported cases, being associated with male victims, younger adults, declared black or brown, with up to 4 years of education, without disabilities or disorders, who had a partner, lived in a rural area, had aggressors aged 25 years or more, female, with an intimate partner, with suspected alcohol use, participation of 2 or more aggressors, occurrence on a public road and single event. Psychological violence was responsible for 7.3% of reports of interpersonal violence and was associated with female victims, aged 50 to 59 years, with at least 9 years of education, without disabilities or disorders, living in an urban or peri-urban area, with aggressors aged 25 or over, male, with an intimate partner, with no suspicion of alcohol use and with a repeat nature. Sexual violence was responsible for 6.2% of registered cases, being associated with females, aged between 20 and 29 years, who did not have a partner, living in urban areas, with an aggressor aged 25 years or more of age, single and unknown perpetrator, and occurrence on a public road. Repeated interpersonal violence, on the other hand, had a prevalence of 56.7% among notifications in this population and was associated with females, aged over 40 years, black and brown, who had a partner, with some disability or disorder, living in urban or peri-urban areas, with aggressors under 25 years of age and of both sexes, with an intimate partner bond with the victim, with the participation of only one perpetrator and occurrence in the residence. Conclusion: Interpersonal violence presented relevant prevalence in the adult population, and its different types were associated with the characteristics of the victim, the aggressor and the occurrence. Its impacts on the daily lives of people and communities create the need for joint and effective actions involving the various sectors of the state and society. In this scenario, public health has a clear role in preventing and managing cases, with the training of professionals and services involved, as well as the strengthening of health systems as strategic tools to combat violence.